SISTEM PENGAMBILAN KEPUTUSAN PENILAIAN WAITERS TERBAIK PADA MENSA VOLKSCAFE MENGGUNAKAN PERBANDINGAN METODE TOPSIS DAN ANP-TOPSIS - Gustillah, Ragil Rachmad; Ardiansyah, Muhammad Dimas; Pratama, Juanda (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
This research develops a decision support system to evaluate the best waiters at Mensa Volkscafe by comparing the TOPSIS and ANP-TOPSIS methods. The TOPSIS method offers advantages in calculation simplicity and its ability to consider various criteria, both subjective and objective, with ease of incorporating important weights. Meanwhile, ANP is a multi-criteria decision analysis method developed from AHP, where each factor and sub-factor are compared, although the calculations become complex with numerous influential factors or sub-factors. The implemented web-based system automates the evaluation process, allowing users to interactively input criteria, alternative, and evaluation values. Five evaluation criteria used are responsibility (K1), punctuality (K2), teamwork (K3), high initiative (K4), and speed in work (K5), with different weights applied for each method. Data was collected through questionnaires from nine waiters at Mensa Volkscafe. The comparison results show differences in the final rankings of the best waiters between the two methods, with Rozatul Jannah ranked first using TOPSIS , and Laurent Simamora ranked first using ANP-TOPSIS. The system's advantages lie in the transparency of the calculation process and the ability to compare the results of both methods, enhancing confidence in the evaluation.